Interaksi Sosial Siswa Non Muslim dan Muslim dalam Lingkungan Sekolah di SMKN 1 Kebumen - Sa'diyah, Mar'atus; Arifah, Umi (IAINU Kebumen, 2024)
The aim of this research is to determine the social interactions of non-Muslim and Muslim students at SMK N 1 Kebumen. The type of approach used is qualitative, field study research design. The research subjects were Islamic Education Teachers, OSIS Supervisors, Rohis Advisors, Deputy Head of Student Affairs, Deputy Head of Curriculum, Head of OSIS, and non-Muslim students. Data collection techniques used trangulation, namely observation, interviews and documentation with data collection techniques, data reduction, data presentation and withdrawal. conclusion. The results of research on social interaction consist of social contact carried out in the classroom, such as social contact in group discussions, social contact in peer groups, while social contact in the school environment is included in organizations and extracurricular activities, such as social contact in the school library, social contact. in the school canteen, social contacts in the OSIS and Rohis organizations. Meanwhile, communication occurs in communication in the classroom, such as communication in academic competitions, communication in class pickets, while communication in the school environment is included in extracurricular activities and organizations such as communication in futsal, communication in OSIS meetings, in scout meetings.